(untitled) (CIPEEX, 2024)
CEREBRAL PALSY (CP) IS A NEUROMOTOR CONDITION THAT AFFECTS THE DEVELOPMENT OF CHILDREN DUE TO PERMANENT BRAIN DAMAGE, OCCURRING IN DIFFERENT FORMS AND DEGREES OF SEVERITY. THE STUDY IN QUESTION WAS A NARRATIVE LITERATURE REVIEW. THE MAIN OBJECTIVE WAS TO ANALYZE AND SUMMARIZE THE PHYSIOTHERAPEUTIC INTERVENTIONS THAT POSITIVELY INFLUENCE THE MOTOR SKILLS OF CHILDREN WITH CP. THE METHODOLOGY EMPLOYED INVOLVED A QUALITATIVE AND UP-TO-DATE BIBLIOGRAPHIC REVIEW, USING SOURCES SUCH AS GOOGLE SCHOLAR, SCIELO, PUBMED, THE VIRTUAL HEALTH LIBRARY (VHL) AND THE MINISTRY OF HEALTH. THE INCLUSION AND EXCLUSION CRITERIA RESULTED IN THE SELECTION OF THIRTEEN SCIENTIFIC ARTICLES RELEVANT TO THE RESEARCH. THE RESULTS FOUND HIGHLIGHTED SEVERAL EFFECTIVE THERAPEUTIC APPROACHES. THE BOBATH NEUROEVOLUTIONARY CONCEPT WAS ASSOCIATED WITH SIGNIFICANT IMPROVEMENTS IN MOTOR FUNCTION AND MUSCLE TONE. APPROACHES SUCH AS THE VIBRATION PLATFORM, GAMETHERAPY AND THE USE OF ZICLAGUE HAVE ALSO SHOWN EFFICACY IN IMPROVING MUSCLE TONE, RANGE OF MOTION AND BALANCE IN PATIENTS WITH CP. OTHER INTERVENTIONS, SUCH AS WHOLE BODY VIBRATION (WBV), THE PEDIASUIT PROTOCOL AND AQUATIC EXERCISES, HAVE SHOWN BENEFITS IN MUSCLE SPASTICITY, POSTURAL CONTROL AND GROSS MOTOR FUNCTION. TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION (TENS) IN COMBINATION WITH THERAPEUTIC EXERCISES WAS EFFECTIVE FOR CHILDREN WITH HEMIPLEGIC CP. IN ADDITION, THE COMBINATION OF TRANSCRANIAL PULSED CURRENT STIMULATION (TCPS) AND TENS RESULTED IN NOTABLE IMPROVEMENTS IN LOWER LIMB SPASTICITY. EQUINE THERAPY WAS ALSO ASSOCIATED WITH IMPROVEMENTS IN POSTURAL CONTROL, MOTOR FUNCTION, BALANCE, MUSCLE SYMMETRY AND SPASTICITY IN PATIENTS WITH CP. AN INNOVATIVE APPROACH USING A RIDING SIMULATOR WAS ALSO FOUND TO BRING SIGNIFICANT IMPROVEMENTS IN MOTOR FUNCTION COMPARED TO CONVENTIONAL THERAPY. PLYOMETRIC EXERCISES ALSO SHOWED BENEFITS IN WEIGHT-BEARING SYMMETRY, MUSCLE STRENGTH, WALKING SPEED, BALANCE AND MUSCLE ACTIVATION IN CHILDREN WITH HEMIPLEGIC CP. IN CONCLUSION, THIS STUDY HIGHLIGHTS THE IMPORTANCE OF PHYSIOTHERAPY IN THE DEVELOPMENT OF MOTOR SKILLS IN CHILDREN WITH CP. THE DIFFERENT INTERVENTIONS MENTIONED OFFER OPPORTUNITIES TO IMPROVE THE QUALITY OF LIFE AND FUNCTIONAL INDEPENDENCE OF THESE CHILDREN. HOWEVER, DUE TO THE HETEROGENEOUS NATURE OF CP AND ITS BREADTH, THERE IS NO SINGLE, EXCLUSIVE METHOD OF NEUROPSYCHOMOTOR TREATMENT, WHICH HIGHLIGHTS THE NEED FOR CONTINUED DEEPENING AND SPECIALIZATION IN THIS AREA. THE RESEARCH PROVIDES A SOLID BASIS FOR GUIDING PHYSIOTHERAPISTS AND MULTIDISCIPLINARY TEAMS IN THE EFFECTIVE TREATMENT OF CP.